2018
DOI: 10.28945/4107
|View full text |Cite
|
Sign up to set email alerts
|

A Grounded Theory for ICT-Mediated Tacit Knowledge Transferability in MNCs

Abstract: Aim/Purpose: A vital business activity within organizations is tacit knowledge (TK) transfer. This work aims to propose a novel framework for TK transferability in multinational corporations (MNCs) from the information and communication technology (ICT) perspective. Background: In the past two decades, researchers have developed several frameworks for TK transfer based on humanistic, business, and educational perspectives. However, a review of the existing work revealed that TK transfer has seldom been examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Fourth, qualitative research provides an opportunity to explore phenomena holistically. The phenomena studied in the field are inseparable because of actions in the area caused by one or two factors but many related factors (Natow, 2020;Sharaf Qdah et al, 2018;Zaluchu, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Fourth, qualitative research provides an opportunity to explore phenomena holistically. The phenomena studied in the field are inseparable because of actions in the area caused by one or two factors but many related factors (Natow, 2020;Sharaf Qdah et al, 2018;Zaluchu, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The author makes various observations to obtain data directly from primary sources, especially to see the location situation. The observation technique used in this study was nonparticipation adjusted to the object or target being observed (M. Rahman, 2020;Sharaf Qdah et al, 2018;Tortia Nurmalasari / Developing Social Capital by the Gintingan Tradition in Jalancagak Community of Subang, West Java et al, 2020). The researcher went directly to the community, but only became an interviewer when collecting data from the people of Bunihayu Village, Jalancagak District.…”
Section: Methodsmentioning
confidence: 99%
“…By counting, the frequency count analysis approach may provide more valid and appealing arguments [46]. Furthermore, this approach was used to tally the number of times the degree of agreement or disagreement was expressed in the research [47]. This expert review research aims to determine the degree of agreement or disagreement on assertions regarding the framework, namely the contributing aspects or dimensions.…”
Section: Validation Of the C19mooc Frameworkmentioning
confidence: 99%
“…Strongly disagree (D3), moderately disagree (D2), slightly disagree (D1), neutral (N), slightly agree (A1), moderately agree (A2), and strongly agree (A3) are the seven degrees of agreement utilized in the questions [46,47]. Combining the A1, A2, and A3 replies yields a percentage of agreement (% Agree).…”
Section: Validation Of the C19mooc Frameworkmentioning
confidence: 99%